Solvothermal Temperature Drives Morphological and Compositional Changes through Dehydroxyfluorination in Anatase Nanoparticles. Issue 1 (23rd December 2016) - Li, Wei; Body, Monique; Legein, Christophe; Borkiewicz, Olaf J.; Dambournet, Damien
Abstract : The reaction system employing titanium alkoxide and hydrofluoric acid under solvothermal conditions has been widely used to prepare anisotropic anatase crystals featuring a large percentage of reactive {001} facets. Nevertheless, such a reaction system leads to the stabilization of both the fluoride and hydroxide‐substituting oxide in the anatase network. The presence of both anions is compensated by the stabilization of titanium vacancies. In this work, we demonstrate that the synthesis temperature not only impacts the morphology of the as prepared nanoparticles but also their chemical composition/structural features. Depending on the reaction temperature, two main crystal growth mechanisms that are anisotropic and/or driven by oriented attachment were observed. The morphological changes are associated with a variation of the composition. Particularly, high temperature allows to eliminate most of the OH groups through oxolation reactions, but fluorine is thermally more stable as demonstrated by 1 H and 19 F solid‐state NMR spectroscopy. This work confirms that the abovementioned reaction system does not lead to pure titanium dioxide, which is an important aspect in linking composition/morphological features to the physico‐chemical properties. Abstract : Anatase is not always a pure oxide: The synthesis temperature in a sol‐gel process performed in the presence of HF induces both compositional and morphological changes with regard to fluoride substitution and oxide anions.